Perspectives on the Training of Human Factors Students for the User Experience Industry. (September 2014) - Gonzalez, Christian A.; Ghazizadeh, Mahtab; Smith, Mac
We surveyed 140 HFES student members and found that nearly 80% of students were considering a future career in UX. In contrast, only 12% felt that their training has prepared them extremely well for a UX career. An analysis of 40 UX job postings revealed that while these positions required some human factors related skills, 37% of their job requirements emphasized design familiarity and programming skills. Students indicated that gaps in their education and preparation represent the largest challenge they face in entering the UX field. They further identified the broad definition of UX and lack of access to industry positions as other challenges in transitioning to UX professionals. It is recommended to focus on increasing HFES's relevance to students interested in future UX careers.